Global Dynamic Impression for Differentiating Between Epileptic and Psychogenic Nonepileptic Seizures: A Feasibility Study - Linor Avraham; Ronen Spierer; Raz Winer; Noam Bosak; Danielle Wasserman; Moshe Herskovitz (Brain and Behavior)
ABSTRACT Objective Medical personnel show difficulty in differentiating psychogenic nonepileptic seizures (PNES) from epileptic seizures (ES). The purpose of this study was to conduct an initial feasibility assessment of the global dynamic impression (GDI) principle and to evaluate its effectiveness in enabling the diagnosis of epileptic versus psychogenic seizures using video footage of events, even by untrained personnel Methods We based this study on video footage showing five videos of PNES and five ES videos. We asked physicians and nurses from the emergency department, internal medicine department, neurology department, and medical students to classify the videos before and after learning the GDI principle. The GDI principle is a simple clinical tool assuming repetitive movements with minimal dynamics in vector and frequency in motor PNES. A correct answer earned a score of 10 points, and a wrong answer a score of 0. Therefore, the questionnaire score could range from 0 to 100. Results A total of 108 medical personnel participated in the study. A total of 42 participants filled out the questionnaire before training—Group 1, and 36 participants filled out the questionnaire after training—Group 2; 30 participants filled out the questionnaire before and after the training—Group 3. The mean score of Group 1 was 55.23 ± 17.83 versus 75.55 ± 13.61 in Group 2 (p = 0.0000001). The mean score of Group 3 was 53 ± 17.8 compared to 78 ± 12.9, before and after training, respectively (p = 0.000001). Significance A brief training on the GDI principle of various medical teams, even unskilled teams, significantly improves differentiating PNES from ES.